Fieldwork, participation and practice : ethics and dilemmas in qualitative research - Laine, Marlene de (SAGE, 2000)
This timely and topical look at the role of ethics in fieldwork takes into account some of the major issues confronting qualitative researchers. The main purposes of this book are twofold: to promote an understanding of the harmful possibilities of fieldwork; and to provide ways of dealing with ethical problems and dilemmas. To these ends, examples of actual fieldwork are provided that address ethical problems and dilemmas, and posit ways of dealing with them.